The incidence of abortion in Nigeria (2015)
CONTEXT—Because of Nigeria’s low contraceptive prevalence, a substantial number of women have unintended pregnancies, many of which are resolved through clandestine abortion, despite the country’s restrictive abortion law. Up-to-date estimates of abortion incidence are needed. METHODS—A widely used indirect methodology was used to estimate the incidence of abortion and unintended pregnancy in Nigeria in 2012. Data on provision of abortion and postabortion care were collected from a nationally representative sample of 772 health facilities and estimates of the likelihood that women who have unsafe abortions experience complications and obtain treatment were collected from 194 health care professionals with a broad understanding of the abortion context in Nigeria. RESULTS—An estimated 1.25 million induced abortions occurred in Nigeria in 2012, equivalent to a rate of 33 abortions per 1,000 women aged 15–49. The estimated unintended pregnancy rate was 59 per 1,000 women aged 15–49. Fifty-six percent of unintended pregnancies were resolved by abortion. About 212,000 women were treated for complications of unsafe abortion, representing a treatment rate of 5.6 per 1,000 women of reproductive age, and an additional 285,000 experienced serious health consequences but did not receive the treatment they needed. CONCLUSION—Levels of unintended pregnancy and unsafe abortion continue to be high in Nigeria. Improvements in access to contraceptive services and in the provision of safe abortion and postabortion care services (as permitted by law) may help reduce maternal morbidity and mortality.